Design of a twelve-bar planar mechanism for finger orthosis - Díaz Montes, J. C.; Vilchis-González, A. H.; Ávila Vilchis, J. C. (Revista Mexicana de Ingenieria Biomedica, 2018)
In the last years, a considerable number of patients with hand mobility problems has been reported; in most of these cases, the patients must spend time in a specialized center to carry out a therapy to rehabilitate damaged parts. This paper presents the design of an orthosis for finger rehabilitation. The novelty of this proposal is that the design is formed by rigid links and three semicircular sliders with a center of rotation coincident with the finger joints; moreover, the synthesis of these sliders is realized in a new and simple way. The mechanism is designed to be compact enough to be used by a person during a whole day; it is formed by twelve links and allows the three finger phalanxes to be flexed simultaneously. The mechanism is coupled only to the dorsal side of the hand and has no interference when grasping objects, in such a way that the orthosis presented in this paper enables the patient to perform the Activities of Daily Living. The synthesis of the mechanism presented in this paper focuses on the middle finger, nevertheless, it is possible to use the same configuration for the others fingers only by scaling.